Analysis of Jefri Nichol's Identity and Image Development on the Instagram Account @Jefrinichol: Analisis Identitas dan Pengembangan Citra Jefri Nichol pada Akun Instagram @Jefrinichol - Arifin, Muchammad Dhani; Rizq Iskandar, Rayhan; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
The phenomenon of identity development in the digital era is increasingly interesting, especially through social media platforms like Instagram. This study aims to analyze how Jefri Nichol builds his identity and image through the Instagram account @jefrinichol. The method used is a descriptive qualitative approach, focusing on content analysis of photo and video uploads as well as interactions with his followers. The research results show that Jefri Nichol consistently leverages Instagram to promote his image as an actor and model while building closer relationships with fans. The novelty of this research lies in the depiction of a dynamic and diverse public identity, as well as how he manages personal narratives behind his public roles, making this study relevant for communication and social media studies.